Evaluating the technical race components during the training season - Arellano, R. (coachesinfo.com, 2000)
At present the analysis of race components during the international swimming competition is a usual activity but it seems insufficient to obtain this type of data only once or twice each year. Our purpose is to show different methods of monitoring these variables: a global method (TSAS), progressive tests and isolated tests. Sample results are shown to see the modifications of the race components after training periods. Isolated specific training drills are necessary to improve these race components, thus the negative improvement observed after the application of traditional no specific training.